AUDIT PEMERINTAH DAN PENGENDALIAN KORUPSI: BUKTI DARI DATA PANEL PROVINSI DI INDONESIA - Shohib Abror; Haryanto Haryanto (Diponegoro Journal of Accounting, 2014)
The purpose of this research is examining the role of government auditing in Indonesia’s corruption control initiatives. The dependent variable is corruption and the independent variables are irregularities and rectivication effort. This study uses population data all provinces in Indonesia. The data used are secondary data, the prosecutor annual reports in 2012 and 2011, IHPS BPK RI (I 2013, II 2012, II 2011) and the Statistical Yearbook of Indonesia 2013. Statistical tools used in this study is multiple linear regression. Statistical hypothesis testing on irregularities per capita concluded that the findings proved significant and negative effect on corruption. Also, rectivication effort per capita proved significant and positive effect on corruption.